2020
DOI: 10.3390/a13100248
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fidelity Gradient-Based Strategy for Robust Optimization in Computational Fluid Dynamics

Abstract: Efficient Robust Design Optimization (RDO) strategies coupling a parsimonious uncertainty quantification (UQ) method with a surrogate-based multi-objective genetic algorithm (SMOGA) are investigated for a test problem in computational fluid dynamics (CFD), namely the inverse robust design of an expansion nozzle. The low-order statistics (mean and variance) of the stochastic cost function are computed through either a gradient-enhanced kriging (GEK) surrogate or through the less expensive, lower fidelity, first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Such a response surface provides an estimation of E[J] and STD[J] and it is constructed leveraging the evaluations of the low-fidelity UQ model, which is cheap but inaccurate, with only few runs of the high-fidelity UQ model, that is more accurate but extremely expensive: this multi-fidelity approach allows to perform UQ estimations accurate as the high-fidelity model at the cost of the lowfidelity one. A detailed description of the present RDO strategy can be found in Serafino et al (2020a). Specifically, here the first order method of moments (Hazelton, 2011) is used as low-fidelity UQ model and the Bayesian Kriging (Wikle and Berliner, 2007) as the high-fidelity one.…”
Section: Figure 4: Workflow Of the Robust Design Optimization Methodo...mentioning
confidence: 99%
“…Such a response surface provides an estimation of E[J] and STD[J] and it is constructed leveraging the evaluations of the low-fidelity UQ model, which is cheap but inaccurate, with only few runs of the high-fidelity UQ model, that is more accurate but extremely expensive: this multi-fidelity approach allows to perform UQ estimations accurate as the high-fidelity model at the cost of the lowfidelity one. A detailed description of the present RDO strategy can be found in Serafino et al (2020a). Specifically, here the first order method of moments (Hazelton, 2011) is used as low-fidelity UQ model and the Bayesian Kriging (Wikle and Berliner, 2007) as the high-fidelity one.…”
Section: Figure 4: Workflow Of the Robust Design Optimization Methodo...mentioning
confidence: 99%
“…22 Some variants apply adaptive refinement only on LFMs, others only on the HFMs, and others on both of them. Tao et al 28 proposed an adaptive scheme which adds a set of points to the HFM DoE; Serafino et al 29 proposed a hybrid strategy with an adaptive refinement which is applied on the HFM based on the EI criterion. An interesting study by Guo et al 30 has shown the impact of the refinement process on the efficiency of the MFMBO.…”
Section: Introductionmentioning
confidence: 99%
“…the uncertain variables usually computed using a combination of adjoint methods and direct differentiation of the governing PDEs. [2][3][4][5] Though the cost of the MoM (with a second-order Taylor expansion) scales only linearly with the number of uncertain variables M, the need to compute high-order derivatives of the QoI w.r.t. the uncertain variables has prevented its widespread use in the industry.…”
Section: Introductionmentioning
confidence: 99%